Answer:
[tex]\begin{array}{cc}x&y\\ \\-2&-1\\0&-2\\2&-3\\6&-5\\9&-6.5\end{array}[/tex]
Step-by-step explanation:
Given:
[tex]y=-\dfrac{1}{2}x-2[/tex]
First, find y for given x:
When x = 0, then
[tex]y=-\dfrac{1}{2}\cdot 0-2\\ \\y=-2[/tex]
When x = 6, then
[tex]y=-\dfrac{1}{2}\cdot 6-2\\ \\y=-3-2\\ \\y=-5[/tex]
When x = 9, then
[tex]y=-\dfrac{1}{2}\cdot 9-2\\ \\y=-4.5-2\\ \\y=-6.5[/tex]
Now find x for given y:
When y = -1, then
[tex]-1=-\dfrac{1}{2}x-2\\ \\-1+2=-\dfrac{1}{2}x\\ \\1=-\dfrac{1}{2}x\\ \\-2=x\\ \\x=-2[/tex]
When y = -3, then
[tex]-3=-\dfrac{1}{2}x-2\\ \\-3+2=-\dfrac{1}{2}x\\ \\-1=-\dfrac{1}{2}x\\ \\2=x\\ \\x=2[/tex]
So, the table is
[tex]\begin{array}{cc}x&y\\ \\-2&-1\\0&-2\\2&-3\\6&-5\\9&-6.5\end{array}[/tex]